Impact of agricultural cooperatives on smallholders' technical efficiency: evidence from Ethiopia - Abate, Gashaw T.; Francesconi, Gian N.; Getnet, Kindie (European Research Institute on Cooperatives and Social Enterprises (EURICSE)., 2013)
Using household survey data from Ethiopia, this paper evaluates the impact of agricultural cooperatives on smallholders' technical efficiency. We utilize propensity score matching to compare the average difference in technical efficiency between cooperative farmers and similar independent farmers. The approach assumes exogenous cooperative formation and similar farm technology across households. The results show that agricultural cooperatives are effective in providing support services that significantly contribute to members' technical efficiency. These results are found to be insensitive to hidden bias and consistent with the idea that agricultural cooperatives enhance members' efficiency by easing access to productive inputs and facilitating extension linkages. Based on the findings, increased participation in agricultural cooperatives should further enhance efficiency gains among smallholder farmers.